Provision of Clean Water Facilities with the Insidence of Diarrhea in the Ujung Pandang Baru Health Center Working Area - Idris, Idris; Pannyiwi, Rahmat; Ula, Zumrotul; Singga, Siprianus (International Journal of Health Sciences, 2023)
The quality of fresh water found in several areas varies greatly depending on the geographical conditions of the region, in mountainous areas most of it contains limestone, in lowland or coastal areas generally the total dissolved solids (TDS) exceeds 500 mg/l while according to Minister of Health Decree no. : 416 of 1990 the maximum limit for TDS in clean water is 500 mg/l so this can be a health problem for residents living in the surrounding area. The aim is to determine the relationship between the provision of clean water facilities and the incidence of diarrhea in the work area of the Health Center. This type of research is analytical observational research, namely to determine the factors related to the provision of clean water and the incidence of diarrhea in the Puskesmas Work Area. Based on the results of the analysis using the chi-square formula, it was found that the value of P = 0.000 < α = 0.05 so it can be concluded that there is a relationship between water quality conditions from a physical aspect and the incidence of diarrhea in the work area of the Health Center. The conclusion is that there is a relationship between the physical quality of water and the incidence of diarrhea in the work area of the Health Center.